FRAILTY INDEX AND INFLAMMATORY MARKERS IN ELDERLY PATIENTS WITH ACUTE SURGICAL ABDOMINAL PATHOLOGIES - Akhverdiev, B.D. (World of Medicine and Biology, 2022)
The purpose of the study was to reveal the relationship between the frailty index and inflammation markers in elderly patients with acute surgical abdominal pathologies. 118 elderly and senile patients (average age was 69.5±0.6 years) were involved in the study. Immediately after admission, the levels of C-reactive protein and interleukin-6 were determined. In addition, at the stage of inclusion of patients in the study, the frailty index was determined using the Edmonton scales. Mean frailty index was 9±0.3. Leukocytes (r=0.574; p=0.000), neutrophils (r=0.434; p=0.000), erythrocyte sedimentation rate (r=0.210; p=0.008), C-reactive protein (r=0.203, p=0.006) and interleukin-6 (r=0.347, p=0.004) had a positive correlation with frailty index. Clinicians evaluating elderly patients with acute abdominal disease should always be aware that elevated serum levels of C-reactive protein and interleukin-6 may be part of the chronic process associated with frailty syndrome in the elderly.
Keywords: fraility index; C-reactive protein; interleukin-6; Edmonton scales; acute abdominal diseases